Hypertensive Disorders of Pregnancy and the Cardiovascular System: Causes, Consequences, Therapy, and Prevention - Baschat, Ahmet A.; Darwin, Kristin; Vaught, Arthur J. (American Journal of Perinatology, 2023)
Hypertensive disorders of pregnancy continue to be significant contributors to adverse perinatal outcome and maternal mortality, as well as inducing life-long cardiovascular health impacts that are proportional to the severity and frequency of pregnancy complications. The placenta is the interface between the mother and fetus and its failure to undergo vascular maturation in tandem with maternal cardiovascular adaptation by the end of the first trimester predisposes to hypertensive disorders and fetal growth restriction. While primary failure of trophoblastic invasion with incomplete maternal spiral artery remodeling has been considered central to the pathogenesis of preeclampsia, cardiovascular risk factors associated with abnormal first trimester maternal blood pressure and cardiovascular adaptation produce identical placental pathology leading to hypertensive pregnancy disorders. Outside pregnancy blood pressure treatment thresholds are identified with the goal to prevent immediate risks from severe hypertension >160/100 mm Hg and long-term health impacts that arise from elevated blood pressures as low as 120/80 mm Hg. Until recently, the trend for less aggressive blood pressure management during pregnancy was driven by fear of inducing placental malperfusion without a clear clinical benefit. However, placental perfusion is not dependent on maternal perfusion pressure during the first trimester and risk-appropriate blood pressure normalization may provide the opportunity to protect from the placental maldevelopment that predisposes to hypertensive disorders of pregnancy. Recent randomized trials set the stage for more aggressive risk-appropriate blood pressure management that may offer a greater potential for prevention for hypertensive disorders of pregnancy.Key Points
Keywords: blood pressure; preeclampsia; prevention; first trimester; cardiovascular disease; hypertension